The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1346/ccmn.1988.0360105
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Trace Element-Substituted Maghemite to Hematite

Abstract: Abstract--X-ray powder diffraction (XRD), transmission electron microscopy, infrared spectroscopy, differential thermal analysis, and surface area (BET) measurements were employed to investigate the transformation of microcrystalline maghemite to hematite. At 500~ pure maghemite was completely altered to hematite in 3 hr, whereas maghemites containing small amounts (< 1%) of Co, Ni, Zn, Cu, Mn, A1, V, and Cr required much longer heating times. The maghemite-to-hematite transformation temperature varied from 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 14 publications
6
58
0
1
Order By: Relevance
“…Hanesch and Scholger (2005) (Jordanova and Jordanova, 1999). The transformation of goethite or ferrihydrite to maghemite takes part during heating (Nørnberg et al, 2004) at temperatures as low as 220°C (Sidhu, 1988). Zanelli et al (in press) observed in-situ formation of maghemite up to 0.5 m deep in soils affected by forest fires in Southern Switzerland.…”
Section: Charred Organic Matter As Colouring Agentmentioning
confidence: 99%
“…Hanesch and Scholger (2005) (Jordanova and Jordanova, 1999). The transformation of goethite or ferrihydrite to maghemite takes part during heating (Nørnberg et al, 2004) at temperatures as low as 220°C (Sidhu, 1988). Zanelli et al (in press) observed in-situ formation of maghemite up to 0.5 m deep in soils affected by forest fires in Southern Switzerland.…”
Section: Charred Organic Matter As Colouring Agentmentioning
confidence: 99%
“…Increasing χ LF values may be due to remnant maghemite components that maintain magnetism, although XRD data only points to the presence of hematite. Increasing Al IS changes the temperature of the solid phase thermal transformation from maghemite to hematite (Sidhu, 1988); therefore even long exposure of maghemites to 500 °C temperature was not able to completely transform maghemite to hematite, and this effect was more pronounced as IS increased.…”
Section: Mass Specific Magnetic Susceptibilitymentioning
confidence: 98%
“…This temperature was chosen based on differential thermal analysis (DTA) and on literature results (Sidhu, 1988). The mullite refractories were placed on a steel tray and then heated.…”
Section: Maghemite-to-hematite Transformationmentioning
confidence: 99%
See 2 more Smart Citations